2005
DOI: 10.1203/01.pdr.0000147565.74947.14
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Dynamic Responses in Children with the Obstructive Sleep Apnea Syndrome

Abstract: Normal children have a smaller upper airway than adults, but, nevertheless, snore less and have less apnea. We have previously shown that normal children have an upper airway that is resistant to collapse during sleep. We hypothesized that this resistance to collapse is due to preservation of upper airway neuromotor responses during sleep. Furthermore, we hypothesized that upper airway responses would be diminished in children with the obstructive sleep apnea syndrome (OSAS). We therefore compared the upper ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 39 publications
8
120
0
2
Order By: Relevance
“…[30][31][32][33][34][35][36] Children with OSA are unable to activate airway tone to maintain airway patency. [37][38][39] The lack of sensation of nasal airflow, as by adenotonsillar hypertrophy or nasal obstruction common in the pediatric population, is associated with increased nasopharyngeal resistance and contributes to OSA, [40][41][42][43][44][45] suggesting that sensation of nasal airflow reduces airway resistance and elicits compensatory increase in pharyngeal tone. 36,46 Therefore, the delivery of heated and humidified air to the nasopharynx at higher than usual flow rates may activate, or reactivate, the protective airway reflex via nasopharyngeal mechanoreceptor or thermoreceptor stimulation, as well as reduce irritation, swelling, and congestion associated with dryness.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Children with OSA are unable to activate airway tone to maintain airway patency. [37][38][39] The lack of sensation of nasal airflow, as by adenotonsillar hypertrophy or nasal obstruction common in the pediatric population, is associated with increased nasopharyngeal resistance and contributes to OSA, [40][41][42][43][44][45] suggesting that sensation of nasal airflow reduces airway resistance and elicits compensatory increase in pharyngeal tone. 36,46 Therefore, the delivery of heated and humidified air to the nasopharynx at higher than usual flow rates may activate, or reactivate, the protective airway reflex via nasopharyngeal mechanoreceptor or thermoreceptor stimulation, as well as reduce irritation, swelling, and congestion associated with dryness.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, researchers reported the prevalence of OSAS in adolescents to be 2% (1), but the prevalence is probably higher in the United States because of the adolescent obesity epidemic (2). OSAS in children is thought to be secondary to a combination of enlargement of the lymphoid tissue (tonsils and adenoid) (3) and, sometimes, obesity, as well as to reductions in neuromuscular tone (4). In adults, there are known anatomic risk factors for OSAS, including enlargement of the tongue, soft palate, parapharyngeal fat pads, and lateral pharyngeal walls (5) in conjunction with craniofacial restriction (retrognathia) (6).…”
mentioning
confidence: 99%
“…In most children, OSAS is related to adenotonsillar hypertrophy or obesity. However, these structural factors cannot fully explain the degree of upper airway collapsibility (1,2). Studies have shown that upper airway neuromotor tone and reflexes during sleep play an important role in maintaining airway patency during sleep in the pediatric population (3,4).…”
mentioning
confidence: 99%